ANALISIS PENGARUH HARGA DAN PROMOSI TERHADAP KEPUASAN PEMBELIAN (Studi Kasus Aplikasi Pesan Antar Makanan Online) - Susbiyantoro, Susbiyantoro; Harjoko, Harjoko; Almakiyah, Shofa Rosita (JAB (Jurnal Akuntansi & Bisnis), 2021)
This study aims to determine the effect of price and promotion on purchasing decisions through the online food delivery application GoFood with the Gojek application. The research sample amounted to 75 respondents were customers. Data was collected through questionnaires, and processing this data using SPSS Version 23.0. The research model used is a descriptive research model which describes systematically and accurately the factors studied. The data testing technique used in this study is the validity test with the calculated r value and the reliability test with Croncbach's Aplha, the data analysis used is linear regression analysis to test and prove the research hypothesis. The results of the study show that price and promotion simultaneously have a positive and significant effect on the decision to purchase GoFood with the Gojek application.Â Keyword: Price, Promotion, Purchase Decision